AGRICULTURAL PRODUCTION INDICATORS AND THE DYNAMIC MACROECONOMIC VARIABLES IN NIGERIA: ARDL MODEL APPROACH - Sunday Brownson AKPAN; Aniefiok Akpan UMOREN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study established the empirical relationship between agricultural production indicators and some key macroeconomic fundamentals in Nigeria. Data (time series from 1961 to 2020) were collected from the World Bank, Food and Agricultural Organization and the Central Bank of Nigeria. The properties of the series were tested with the Augmented Dickey-Fuller unit root test and improved ADF-GLS unit root test. The Autoregressive Distributed Lag Model (ARDL) was used to establish the existence of the cointegration among the specified series. The empirical results revealed that, the per capita real GDP, land density and consumer price index are the determinants of crop production gross index in the long run, whereas, per capita income, lending rate, land density and total import are the short run determinants. Also, the per capita income, land density, consumer price index and the nominal exchange rate influence the agricultural gross production index in the long run; while the per capita income and land density were the short run determinants. Moreover, land density, per capita income and balance of trade were found to determine the livestock gross production index in the long run; while the lending rate, land density and inflation rate were the short run determinants. Based on the findings, it is recommended that, specific policy to focus on the improvement of the per capita income, restricted trade policy and reduction and or stabilization of inflation rate in the country are inevitable. The lending interest rate should be regulated to provide more credit to the agricultural sector.